2012
DOI: 10.1111/j.2047-6310.2012.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity assessment of a portable bioimpedance scale to estimate body fat percentage in White and African–American children and adolescents

Abstract: Objective To determine accuracy of the Tanita SC-240 body composition analyzer to measure pediatric percent body fat (%BF). Methods Eighty-nine African American and white 5–18 year-olds participated in this study. %BF was estimated by DXA and by the Tanita SC-240. Results Overall %BF was 33.5 ± 10.5% (Tanita SC-240) versus 34.5 ± 8.7% (DXA). There was no significant difference between the two measures (p = 0.52, average error = −1.0%, average absolute error = 3.9%). The Tanita mean %BF estimates significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 12 publications
4
76
0
3
Order By: Relevance
“…Body mass and percentage body fat (% body fat) were measured with the Tanita SC-240 bio-electrical impedance scale (Arlington Heights, IL, USA), which has demonstrated acceptable validity for field studies [19]. Height was measured with a Seca 213 portable stadiometer (Hamburg, Germany) [14].…”
Section: Methodsmentioning
confidence: 99%
“…Body mass and percentage body fat (% body fat) were measured with the Tanita SC-240 bio-electrical impedance scale (Arlington Heights, IL, USA), which has demonstrated acceptable validity for field studies [19]. Height was measured with a Seca 213 portable stadiometer (Hamburg, Germany) [14].…”
Section: Methodsmentioning
confidence: 99%
“…We previously conducted a validation study of the Tanita SC-240 scale among White and African American children and the results demonstrated that the scale had acceptable accuracy for estimating PBF in field studies. 13 However, the degree to which the validity of the scale varied across sites and may have impacted the results is not known. Each BIA device uses proprietary equations to estimate body fat, and this may impact the level of adiposity obtained with each device; however, this is unlikely to impact the comparisons among countries given that the same scale was used at all research sites.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition was estimated by bioelectrical impedance analysis (BIA) using the Tanita Ò SC-331s Total Body Composition Analyzer, which has been validated for children of 5 years old or more. 47 Briefly, BIA measures the electrical impedance, which is the resistance of body tissues to an electric flow. This allows estimating the body weight as well as fat and lean masses (in kg and percentage).…”
Section: Children Clinical Data and Samplesmentioning
confidence: 99%